Waste cooking oils exploitation targeting EU 2020 diesel fuel production: Environmental and economic benefits. (10th May 2019) - Chrysikou, Loukia P.; Dagonikou, Vasiliki; Dimitriadis, Athanasios; Bezergianni, Stella
Abstract: The present paper aims to investigate the environmental and economic impacts of co-processing petroleum fractions with bio-based feedstocks for direct refinery integration versus the conventional drop-in integration of biofuels with compatible transportation fuels. Three different pathways of market diesel (commercial diesel fuel from a typical fuel station in Greece) production with 10% v/v biocontent (biomass feed) were explored by variant biomass utilization with fossil counter parts (diesel fuel). The first case study depicts the current market diesel production process via blending petroleum fractions with FAME (Fatty Acids Methyl Esters) biodiesel. The second case study involves the production of market diesel from blending petroleum fractions with hydrotreated residual lipids (Waste Cooking Oil, WCO), while the third case study explores the alternative approach of co-processing petroleum fractions with WCO. In all cases, the market diesel production chain was based on the hydrotreating process simulated using Aspen Plus. The results have shown that the most beneficial case, by environmental and economic viewpoint, for market diesel production with 10% v/v biocontent in the Greek market is co-processing of petroleum fractions with WCO. This approach accounts for a reduced production cost (751 €/m 3 ) and environmentally friendly profile (243 kgCO2 -eq/m 3 ) compared with the other two case studies. Additionally co-processing of residual biomass with petroleum fractions utilizes existing infrastructure towards the production of sustainable fuels, rendering this pathway more attractive form a CAPEX point of view. Graphical abstract: Image 1 Highlights: Three production technologies of 10% bio-content diesel are evaluated. Hybrid diesel reduces GHG emissions by ∼24% compared to current market diesel. Renewable fuels are economically attractive for waste oil prices below 725 €/m 3 . Co-processing reduces the production cost of current market diesel by 6%.